Production and characterization of natural rubber-Ca/P blends for biomedical purposes - Nascimento, R. M. [UNESP]; Faita, F. L.; Agostini, D. L. S. [UNESP]; Job, A. E. [UNESP]; Guimaraes, F. E. G.; Bechtold, I. H. (Elsevier B.V., 2014)
This study presents the development of natural rubber-Ca/P blends, as promising candidates for biomedical purposes. The specific objective was the incorporation of Ca/P into a natural rubber polymeric matrix. Ca/P crystalline phases were synthesized by the sol-gel method and the polymeric matrices were produced using natural rubber extracted from latex of the Hevea brasiliensis. The shape and size of natural rubber particles present in the NR membrane, as well as, the way the Ca/P powder grains aggregate in the polymeric matrix were investigated, giving information about the interactions between the Ca/P and the natural rubber particles. Confocal fluorescence scanning microscopy measurements allowed us to propose a structure where the Ca/P grains are surrounded by natural rubber particles. This structure may mediate Ca2+ release for tissue regeneration. The system investigated may open new horizons for development of a bandage which provides the controlled-release of biomaterials. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Natural rubber; Calcium phosphate; Biomaterial; Tissue regeneration